EFFECT OF LIME JUICE (CITRUS AURANTIFOLIA) ON BLOOD URIC ACID LEVELS IN ELDERLY - Ika Purwaningrum; Sulasmi Sulasmi (UNIVERSITAS SARI MUTIARA INDONESIA, 2022)
Health problems commonly experienced by the elderly are quite complex along with the changes they experience biologically or psychosocially. Some of the health problems that commonly occur include arthritis or joint inflammation, which is a disease that attacks the joints. This inflammation can occur due to many factors, one of which is uric acid levels. The elderly are one of the groups that are susceptible to diseases including arthritis (Gout). Gout is a disease that arises due to excessive blood uric acid levels. When uric acid levels are high in the blood, it is called hyperuricemia. The cause of excessive blood uric acid levels is the production of uric acid in the body more than its disposal. Uric acid in the blood can be excreted through urine. The purpose of this study was to determine changes in uric acid levels before and after treatment of lime juice (Citrus aurantifolia).This research method is an experimental research research design Pre and Post Test Group Design without control. The study was conducted at the 'Aisyiyah Elderly Homes, Surakarta in July 2021.The results showed that the distribution was mostly in elderly women, namely 20 people. There is a significant difference in uric acid levels before and after treatment of lime juice (Citrus aurantifolia) which is indicated by the p value = 0.000, where the p value <0.05.The conclusion of this study is the effect of giving lime juice (Citrus aurantifolia) to changes in blood uric acid levels.